IS 360° INTRAOPERATIVE LASER RETINOPEXY AFTER PRIMARY PARS PLANA VITRECTOMY WORTHWHILE TO PREVENT RECURRENT RETINAL DETACHMENT? - Maslik, Marouane; Abaaqil, Younes; Belghmaidi, Sarah; Hajji, Ibtissam; Moutaouakil, Abdeljalil (Indonesian Vitreoretinal Society, 2023)
Introduction: To determine if performing 360° laser retinopexy anterior to the equator during surgery is a viable option to prevent recurrent retinal detachment following a primary pars plana vitrectomy for rhegmatogenous retinal detachment. Methods: A consecutive case series of 142 patients with retinal detachment who underwent vitrectomy by a single surgeon in Mohammed VI university hospital Marrakech hospital between January 2020 and December 2021. A comparison was made between a group of consecutive patients who underwent 360° laser retinopexy and a control group of patients who did not receive the treatment (39). Patient demographic and clinical information was gathered from medical records. Both groups were analyzed and compared in terms of baseline characteristics and the risk of recurrent retinal detachment over time. Result: Prophylactic intraoperative 360° laser treatment was performed on 103 RRD cases (52 years) and compared to a control group of 39 RRD cases (56.8 years). The rate of the incidence of recurrent retinal detachment at six months after surgery was 12.6%( 13/103 eyes) in the 360° laser group and 28.2%(11/ 39 eyes) in the control group. Conclusion: Intraoperative 360° laser retinopexy performed after primary pars plana vitrectomy led to a substantial decrease in the rate of recurrent retinal detachment post-surgery.